Social structures, sexual division of labor and methodological approaches Family structure and the social and health role of women - Siles González, José; Solano Ruiz, Carmen (Investigación y Educación en Enfermería, 2010)
Social structures, sexual division of labor and methodological approaches Family structure and the social and health role of women